Climate policy and the 'carbon haven' effect. (6th August 2013) - Branger, Frédéric; Quirion, Philippe
Abstract : In a world with uneven climate policies, the carbon price differentials across regions could shift the production of energy‐intensive goods from carbon‐constrained countries to 'carbon havens', or countries with laxer climate policy. This would reduce the environmental benefits of the policy (carbon leakage) while potentially damaging the economy (competitiveness concerns). A review on these questions is provided in this article. First we discuss the main terms involved, such as carbon leakage, competitiveness, sectors at risk, or climate spillovers. Then we analyze the studies evaluating the carbon leakage risk. Most ex ante modeling studies conclude to leakage rates in the range of 5–20% (if no option to mitigate leakage is implemented), whereas ex post econometric studies have not revealed statistically significant evidence of leakage. Different policy options to face these issues are then examined with an emphasis on Border Carbon Adjustments (BCA). BCA consist in reducing the carbon price differentials of the goods traded between countries. Properly implemented, they can reduce leakage (by around 10 percentage points in ex ante modeling studies) in a cost‐effective way but are controversial because they shift a part of the abatement costs from abating countries to nonabating countries. Their impact on international negotiations is unclear: they could encourage third countries to join the abating coalition or trigger a trade war. Besides, their consistency with World Trade Organization (WTO) rules is contentious among legal experts. WIREs Clim Change 2014, 5:53–71. doi: 10.1002/wcc.245 This article is categorized under: Climate Economics > Economics of Mitigation